Effect of control on the duct flow at high mach numbers - Aabid, Abdul; Khan, Sher Afghan; Baig, Maugal Ahmed Ali; Rao, K Srinivasa (IOP Publishing, 2021)
Once the stream is drained through a nozzle, this research explores the pressure in a circular duct. This research investigates when the control is triggered, the pressure in the tube, and flow development. At the base, the flow regulators as tiny jets are used at PCD of 0.013 m, and the orifice radius is 0.5 mm. The flow variables are Mach (M) and the NPR. The investigation was done for M = 2.1 & 2.8. The expansion level was from 3 to 11. The duct area ratio used is 6.25. The duct length varied from 10 to 1. For M = 2.1, the tested NPRs were at different expansion levels. When they are under the impact of under-expansion, flow oscillations are noticed. At NPR 3, an adverse pressure exists at Mach 2.1, and similar patterns too seen for higher NPRs. The flow's wavy nature is dying out with the decrease in pipe length, and pressure recovery is smooth. The control regulator has not influenced the flow adversely.